1995
DOI: 10.1007/bf00858971
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of children with moderate chronic renal failure

Abstract: Nutritional status was evaluated in 15 children (11 males) with moderate chronic renal failure (CRF). Two 3-day prospective dietary records, anthropometric measures and biochemical determinations were performed 3 months apart. Energy, protein, carbohydrate, fat, polyunsaturated, monounsaturated and saturated fatty acid intakes, expressed as percentages of international recommendations, were 87 +/- 14, 223 +/- 42, 73 +/- 12, 110 +/- 27, 55 +/- 31, 129 +/- 51 and 111 +/- 26%, respectively. The relative distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…They were included in the study if they had completed at least 12 months of EF. Their diagnoses were renal dysplasia [20], posterior urethral valves [9], occult neuropathic bladder with reflux nephropathy [1], congenital nephrotic syndrome [1], cortical necrosis [1], interstitial nephritis [2] and bilateral Wilms tumour [1]. In addition 6 children had major co-morbid conditions: 4 had congenital heart disease requiring major surgery in the first 4 months of life (coarctation of the aorta, ventricular septal defect, total anomalous pulmonary venous drainage and complex cyanotic heart disease), 1 had the CHARGE association [10] and 1 microcephaly associated with severe developmental delay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were included in the study if they had completed at least 12 months of EF. Their diagnoses were renal dysplasia [20], posterior urethral valves [9], occult neuropathic bladder with reflux nephropathy [1], congenital nephrotic syndrome [1], cortical necrosis [1], interstitial nephritis [2] and bilateral Wilms tumour [1]. In addition 6 children had major co-morbid conditions: 4 had congenital heart disease requiring major surgery in the first 4 months of life (coarctation of the aorta, ventricular septal defect, total anomalous pulmonary venous drainage and complex cyanotic heart disease), 1 had the CHARGE association [10] and 1 microcephaly associated with severe developmental delay.…”
Section: Methodsmentioning
confidence: 99%
“…However in practice it is often difficult to provide a "safe" nutritional intake and variable results have been reported with either oral energy supplements or enteral feeding (EF) [4][5][6][7]. Previous studies have clearly shown an inadequate spontaneous energy intake in children with CRF without intervention and a protein intake which exceeds the recommended dietary allowance (RDA) without specific dietary advice [8,9]. EF has been an integral part of the care of infants and children with CRF/ESRF at Great Ormond Street Hospital for Children since 1989, and this study retrospectively describes our long-term experience of EF, evaluating weight gain and linear growth, nutritional intake, biochemical parameters and outlook for normal feeding.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Norman et al [27], serum phosphorus levels in the children with GFR below 25 mL/min/1.73 m 2 were higher compared to those with GFR above 25 mL/min/1.73 m 2 , but serum calcium levels were not different between these two groups. Another study demonstrated that serum calcium and phosphorus levels were not different between the groups of GFR less and above 50 mL/min/1.73 m 2 [31]. In this study, serum calcium levels in the group of GFR below 75 mL/min/1.73 m 2 was lower compared to the group of GFR above 75 mL/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 40%
“…Adequate nutrition and frequent adjustments of the nutritional prescriptions are important to achieving adequate nutritional intakes for normal pubertal growth in children with CRF. 23,24 Orejas et al 25 reported a normal anthropometric status in a group of children with moderate CRF. Our data, however, have shown significant differences in SH, LL, and CC between well-nourished children with mild to moderate CRF and healthy controls, even when they were in the same nutritional category.…”
Section: Discussionmentioning
confidence: 97%